SOCIAL-RIGHTS ASPECTS OF EXTERNAL WORK MIGRATION AND TRAFFIC OF THE POPULATION OF UZBEKISTAN - Rakhmatullaev Shavkatjon Mukhammadalievich (Web of Journals Publishing, 2025)
The complex, sometimes contradictory processes that have taken place in the so-cial and economic life of Uzbekistan over the past three decades, associated with the transition to market relations, have had a negative impact on the unemployment rate and the increasing flow of illegal migrants from the country to countries with more favourable conditions for earning a living. The gradual increase in labour migration has, in most cases, become illegal. It is well known that illegal migrants are often hired for casual work, often in dangerous conditions without any legal protection, putting their personal safety and health at risk.